Family well-being index report (National Population and Family Development Board, 2011)
This study has identified suitable indicators that can provide information about the well-being of families in Malaysia. Subsequently, based on the identified indicators, a Family Well-Being Index (FWI) was developed to measure the current well-being of the family as well as to be used in policy formulation, planning for implementation of future research, the development of new programmes and services, and expansion of the existing programmes.